Atrioventricular nodal ablation in patients with resynchronization therapy and atrial fibrillation – long term results. (4th May 2017) - Aune, Arleen; Færestrand, Svein; Hoff, Per Ivar; Schuster, Peter
Abstract: Objectives . Atrioventricular nodal ablation (AVNA) is recommended for patients (pts) with cardiac resynchronization therapy (CRT) having atrial fibrillation (AF) and incomplete ventricular capture (Class IIa, level B). AVNA reduces mortality and improves the New York Heart Association (NYHA) functional class during intermediate term follow-up. The objectives were to study the long-term outcome regarding quality of life (QoL) and survival of our CRT pts after AVNA. Design. 37 CRT-pts undergoing AVNA due to inadequate biventricular pacing were included in the study. Data were retrospectively obtained from clinical records and through telephone interviews. Results . Twenty pts died during the follow-up period of average 30.6 ± 24 months. After AVNA the ventricular capture improved significantly from 68.4 ± 23% to 98.5 ± 2% (p < 0.001). A significant and sustained improvement of average 0.3 ± 0.5 (p = 0.001) in NYHA functional class was found. Additionally a large percentage of pts discontinued taking rate reducing drugs with potential severe side effects. Conclusion . AVNA in CRT pts was safe and effective. The treatment resulted in a sustained improvement in QoL, including long-term improvement in NYHA functional class.